Exclusion of Sexual Minorities in Sexual Health Education in Zambia - Libati Mundia; Chitabanta Jonathan; Mwale Ackson (European Scientific Journal, ESJ, 2019)
Background: Sexual health interventions against sexual contraction and transmission of HIV in most developing countries such as Zambia, are often biased towards heterosexual sexual health interventions. This act tends to exclude minority sexual groups such as men who have sex with men whose existence could affect the transmission and spread of the virus. This paper therefore sought to present an analysis of the exclusion of sexual minorities in sexual health education interventions in Zambia. Methods: This paper employed a desk-based-research study and relied mainly on the review of secondary data in form of Ministry of Health (MOH) and National Aids Council (NAC) strategic documents and scholarly journals, articles and research papers relevant to the topic. Results: A knowledge gap on sexual health education exists amongst the sexual minority groups in the few studies assessed. This can be attributed to the fact that the Zambian society is believed to be heterosexual with most interventions adopting a heterosexual stance towards sexual health education. Limited thought to the sexual health concerns of men who have sex with men in Zambia can be attributed to criminal laws against acts of homosexuality, societal disdain for acts of a non-heterosexual nature, and religious teachings against acts of a non-heterosexual nature. Lack of consideration of sexual minorities and their sexual activities may have serious effects on their sexual health knowledge levels and sexual practices. Conclusion: Legal, societal and religious opposition must be addressed to enable open public discussion and debates on the design of more representative sexual health education.